Cavity-based high-efficiency and wideband 90° polarization rotator - Wang, Jiang (2016)
We present a high-efficiency wideband 90° polarization rotator based on 2D array of substrate integrated waveguide cavities etched with three twisted slots, which can rotate a horizontally polarized incident wave into an outgoing vertically polarized wave. The twisted slots etched on the surface of the cavity are utilized to couple the wave into and out of the cavity with the polarization direction rotated. As a proof-of-concept, a prototype of the proposed rotator is fabricated and measured in the microwave regime. The proposed 90° polarization rotator features a low insertion loss of about 0.5 dB in the pass band with a factional bandwidth of 28.6%, as well as high polarization rotation efficiency of over 90%.